Sosialisasi Online Dampak Negatif Media Sosial Bagi Remaja - Pivit Septiary Chandra; Sonia Sischa Ekaputri; Abdiana Ilosa; Arridho Abduh; Ilham Chanra Putra (MENARA RIAU, 2021)
Technology and social networks, or what we often call cyberspace, have become part of social life in the real world. social media can be found with the help of computer technology, laptops, smartphones and other communication media. The use of social media has been used at various levels of society and various groups for media interaction or promotion from children, adolescents, to adults. Adolescence is a period of transition from childhood full of dependence to a period of forming responsibilities. In its use, social media is used mostly by adolescents, with this transitional period adolescence becomes a special concern because it will affect their behavior and personality in the future. The purpose of this service is to provide knowledge and insights to adolescents on social media and its effects, to provide learning for the community in responding to social media. The method is carried out with a lecture system with a preventive approach to the audience against the values given by the speaker.